Retrospective study of mesenteric ischemia - Mandapati, Mallikarjuna Reddy; Jukuri, Sanjeev Kumar; Nasika, Nageswara Rao; Neshat, Haleema (International Surgery Journal, 2020)
Background: Acute mesenteric ischemia (AMI) is typically defined as a group of diseases characterized by an interruption of the blood supply to varying portions of the small intestine, leading to ischemia and secondary inflammatory changes. Methods: A monocentric retrospective study was conducted between 01 August 2013 and 31 December 2019; 24 AMI patients underwent surgery (17 men and 7 women). Retrospectively, the risk factors, management until diagnosis and mortality were evaluated. Results: Patients present with an acute pain of the abdomen. Diagnosis was provided by CT with contrast medium. The 30-day mortality was 45.8%, the late mortality was 25% and the overall mortality was 70.8%. For the <12 hours delay group, the mortality was 33.3%, and the mortality in the group with 12-24 hours delay was 80% and was 87.5% in the >24 hours after admission group. Conclusions: If untreated, this process will eventuate in life threatening intestinal necrosis. The incidence is low, estimated at 0.09-0.21% of all acute surgical admissions.